Bivalirudin Versus Heparin During Percutaneous Coronary Intervention in Patients With Acute Myocardial Infarction - Patel, Hiten (Cardiol Res, 2019)
BACKGROUND: The aim of the study was to compare the efficacy and safety of bivalirudin versus unfractionated heparin (UFH) in patients with acute myocardial infarction who undergo percutaneous coronary intervention (PCI). Earlier trials comparing bivalirudin and UFH during PCI demonstrated that bivalirudin caused less bleeding with more stent thrombosis. Since then, adjunct antiplatelet strategies have evolved. Improved upstream platelet inhibition with potent P2Y12 inhibitors decreased the need for routine glycoprotein IIb/IIIa inhibitor (GPI), resulting in similar outcomes among UFH and bivalirudin. Therefore, the role of bivalirudin in modern PCI practices is questionable. METHODS: We utilized Cochrane Review Manager (RevMan) 5.3 to perform a meta-analysis of seven randomized controlled trials (RCTs) with 22,844 patients to compare bivalirudin to UFH in patients with acute myocardial infarction requiring revascularization. RESULTS: There was no difference between bivalirudin and UFH regarding major adverse cardiac events (MACE), risk ratio (RR) 0.99, 95% confidence interval (CI) 0.87 - 1.12; P = 0.83) or cardiovascular mortality (RR 0.87, 95% CI 0.71 - 1.07; P = 0.18). Bivalirudin increased acute stent thrombosis (RR 2.77, 95% CI 1.49 - 5.13; P = 0.001), which was only significant among ST-elevation myocardial infarction (STEMI) only trials. Bivalirudin caused less major bleeding (RR 0.66, 95% CI 0.49 - 0.90; P = 0.007), which was negated when GPI was used provisionally (RR 0.93, 95% CI 0.64 - 1.33; P = 0.67). CONCLUSIONS: Among patients with acute myocardial infarction who underwent PCI, bivalirudin and UFH demonstrated similar MACE and cardiovascular mortality. Bivalirudin increased acute stent thrombosis, which was more remarkable among STEMI. Bivalirudin decreased major bleeding, but this benefit was negated when GPI was used provisionally.